Challenges in Using Big Data to Develop Decision Support Systems for Social Work in Germany. Issue 2 (3rd July 2019) - Schneider, Diana; Seelmeyer, Udo
Abstract: Nowadays, big data analytics are increasingly replacing human decision-making processes in practice fields. In the welfare context, however, they are still being explored only marginally. The following theoretical discussion draws on the example of the MAEWIN project to explore the challenges of using big data when developing decision support systems in the context of social work. The project reveals some similarities with the well-known challenges of big data research (e.g., with regard to data protection, bias, and handling probabilities). However, it also has to face further challenges such as the different knowledge approaches within social work.